Biology of rediscovered rare endemic Cota fulvida (Grierson) Houlb. in Eski?ehir-Turkey - Koyuncu, Onur; Erkara, Ísmühan Potoglu; Yaylaci, Ö Koray; Ocak, Atila; Osoydan, Kadir; Özgisi, Kurtulus (Bangladesh Journal of Botany, 2013)
The present study determines the morphological, anatomical, palynological, karyological, chorological features and conservation status of the rediscovered rare endemic Turkish taxon Cota fulvida (Grierson) Holub. (Asteraceae) after ca.110 years. C. fulvida distributes naturally in Gölcük Plateau (Türkmen Mountain), Eski?ehir-Turkey. In the cross-sections of the root of C. fulvida, the pith was found completely covered by xylem cells. As to stem, it was observed that large parenchymatic cells were present in the pith of the stems. Leaves are equifacial and amphistomatious having amaryllis type of stomata. They are mesomorphic. Stomata are anisocytic. The results of the light and scanning electron microscope investigation revealed that the pollen grains of C. fulvida are tricolporatae, amb shape triangular, pollen shape spheroidal. Exine tectatae-echinate. The somatic chromosome number of C. fulvida was found to be 2n =18 without any satellite. It is considered "Critically Endangered" (CR) based on IUCN category.